2014
DOI: 10.1111/pbi.12306
|View full text |Cite
|
Sign up to set email alerts
|

Rice transgene flow: its patterns, model and risk management

Abstract: SummaryProgress has been made in a 12 year's systemic study on the rice transgene flow including (i) with experiments conducted at multiple locations and years using up to 21 pollen recipients, we have elucidated the patterns of transgene flow to different types of rice. The frequency to male sterile lines is 10 1 and 10 3 higher than that to O. rufipogon and rice cultivars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
(77 reference statements)
0
12
0
Order By: Relevance
“…() reported that the maximum frequency of gene flow between rice cultivars and O. rufipogon was up to 3%, and the maximum distance over which gene flow was observed was 43.2 m in natural habitats at Hunan Province, China. A large‐scale (1.3–2.4 ha) rice gene‐flow study reported that the highest frequency of transgene flow from transgenic rice plants to O. rufipogon was up to 11.24% in Sanya (Hainan, China, at 1 m) and 18.00% in Guangzhou (Guangdong, China, at 0 m), and the maximum distance of transgene flow was 50 m (0.076%) and 250 m (0.008) at Guangzhou and Sanya, respectively, with the detection limit of 0.01% (Jia et al ., ). Some short‐term studies showed that once exogenous genes escape from transgenic rice to wild relatives, they can be stably inherited and expressed, suggesting the exogenous genes might persist in wild rice populations (Song et al ., ; Su et al ., ).…”
Section: Issues Facing Adoption Of Bt Rice In Chinamentioning
confidence: 97%
See 2 more Smart Citations
“…() reported that the maximum frequency of gene flow between rice cultivars and O. rufipogon was up to 3%, and the maximum distance over which gene flow was observed was 43.2 m in natural habitats at Hunan Province, China. A large‐scale (1.3–2.4 ha) rice gene‐flow study reported that the highest frequency of transgene flow from transgenic rice plants to O. rufipogon was up to 11.24% in Sanya (Hainan, China, at 1 m) and 18.00% in Guangzhou (Guangdong, China, at 0 m), and the maximum distance of transgene flow was 50 m (0.076%) and 250 m (0.008) at Guangzhou and Sanya, respectively, with the detection limit of 0.01% (Jia et al ., ). Some short‐term studies showed that once exogenous genes escape from transgenic rice to wild relatives, they can be stably inherited and expressed, suggesting the exogenous genes might persist in wild rice populations (Song et al ., ; Su et al ., ).…”
Section: Issues Facing Adoption Of Bt Rice In Chinamentioning
confidence: 97%
“…Some short‐term studies showed that once exogenous genes escape from transgenic rice to wild relatives, they can be stably inherited and expressed, suggesting the exogenous genes might persist in wild rice populations (Song et al ., ; Su et al ., ). However, a recent 12‐year systemic study suggested that F 1 hybrids of transgenic rice/ O. rufipogon gradually disappeared within 3–5 years and that the transgene was not detectable in the mixed population, suggesting the O. rufipogon may possess a strong mechanism of reproductive isolation for self‐protection (Jia et al ., ). Therefore, Jia et al .…”
Section: Issues Facing Adoption Of Bt Rice In Chinamentioning
confidence: 97%
See 1 more Smart Citation
“…; Jia et al. ). Gene flow results collected from these experimental studies are the first step for assessing the impact of crop‐to‐weed and crop‐to‐wild transgene flow in rice.…”
Section: Gene Flow: From Cultivated To Weedy Ricementioning
confidence: 98%
“…Using a similar transgene marker, Jia et al. () investigated the frequency of gene flow from the crop into two weedy rice populations: one in Leizhou of Guangdong province, the other in Yangzhong of Jiangsu province. The estimated gene flow ranged from 0.002% to 0.342%.…”
Section: Gene Flow: From Cultivated To Weedy Ricementioning
confidence: 99%